2010
DOI: 10.1007/s11655-010-9999-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xuefu Zhuyu Capsule (血府逐瘀胶囊) on the symptoms and signs and health-related quality of life in the unstable angina patients with blood-stasis syndrome after percutaneous coronary intervention: A Randomized controlled trial

Abstract: Compared with SM Capsule treatment, a short-term treatment with XFZY Capsule exhibits better efficacy on CSS and BSS scores, and HR-QOL in UA patients with BSS after PCI. However, its long-term efficacy and safety still needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…The experience has exemplified the tolerance, dependence, and assimilation of not only two medicines but also other science disciplines in IM (Xu and Chen, 2008), and provided a paradigm for worldwide IM (Dobos and Tao, 2011;Robinson, 2011). IM has shown potential benefit on alleviating clinical symptoms, reducing post-PCI restenosis, enhancing quality of life and improving post-PCI myocardial perfusion in CAD patients (Chen et al, 2006;Li et al, 2009;Qin and Huang, 2009;Zhang et al, 2009;Chu et al, 2010;He et al, 2010), while its role in second prevention of CAD and its effect on reducing MACEs remains unclear. In this prospective study, 5284 CAD patients were enrolled and logistic regression analysis showed that IM treatment and statins were the independent protective factors and could reduce the risk of MACEs by 31% and 77% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The experience has exemplified the tolerance, dependence, and assimilation of not only two medicines but also other science disciplines in IM (Xu and Chen, 2008), and provided a paradigm for worldwide IM (Dobos and Tao, 2011;Robinson, 2011). IM has shown potential benefit on alleviating clinical symptoms, reducing post-PCI restenosis, enhancing quality of life and improving post-PCI myocardial perfusion in CAD patients (Chen et al, 2006;Li et al, 2009;Qin and Huang, 2009;Zhang et al, 2009;Chu et al, 2010;He et al, 2010), while its role in second prevention of CAD and its effect on reducing MACEs remains unclear. In this prospective study, 5284 CAD patients were enrolled and logistic regression analysis showed that IM treatment and statins were the independent protective factors and could reduce the risk of MACEs by 31% and 77% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For centuries, TCM physicians have prescribed Xue-Fu-Zhu-YuTang, a famous TCM formula, for treating cardiovascular diseases. Clinically reliable therapeutic effects have been achieved for atherosclerosis and coronary artery diseases (Chu et al, 2010;Hoa et al, 2006). According to a previous study, Xue-Fu-Zhu-YuTang has been reported to induce endothelial progenitor cell angiogenesis and hasten tube formation, particularly in capillary vessels, and to potentiate rt-PA-mediated neuroprotection against thromboembolic stroke in rats .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that some kinds of herbal medicine, such as Xuefu Zhuyu Capsule [17], exhibit better efficacy on HRQoL in patients with unstable angina after PCI. However, the application of TCM in the post-PCI patients still lacks support from rigorously designed clinical trial.…”
Section: Discussionmentioning
confidence: 99%